ETOS KERJA DAN BUDAYA ORGANISASI ISLAMI DI BMT MITRA MUAMALAH JEPARA - Susilo, Edi (IAIN Tulungagung, 2019)
Mitra Muamalah BMT (MitraMu) Jepara is one of the Sharia Microfinance Institutions incorporated as Cooperatives (KSPPS). This BMT has grown rapidly and has sixty (60) employees. Employee performance is influenced by the work ethic and Islamic corporate culture implemented. The Islamic work ethic is seen from the indicators of discipline, honesty, loyalty, responsibility, creativity and orderliness of Islamic administration. Islamic organizational culture can be seen from sharia compliance and team collaboration to achieve institutional goals. By implementing the work ethic and Islamic culture, there has been an increase in the performance of employees over time, solidity and brotherhood (ukhuwah) and the Islamic morals of employees are increasingly showing improvement.